Book Review - 2052: A Global Forecast for the Next Forty Years - Michael Marien (Cadmus, 2012)
2052: A Global Forecast for the Next Forty Years is a report to the CoR commemorating the 40th anniversary of The Limits to Growth, written by one of the four original authors. This broad forecast is “an informed guess tracing the big lines in what I see as the probable global evolution toward 2052…the most likely global roadmap to 2052 so that I would know what I am in for.” Since publication of The Limits to Growth in 1972, “humanity remains in solid overshoot…and we can discern the early signs of the coming gradual destruction of the ecosystem” (p.xv).